Seeking new prognostic and predictive factors in patients with metastatic renal cell carcinoma – hypoxiainduced factors - Młot, Beata; Szczylik, Cezary; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Malignant tumours of the kidneys are relatively rare tumours that occur in adults, although there has been a constant increase in the incidence of this cancer type in recent years. It occupies the 10th place in terms of the number of new cases of cancer in men and 14th place in women. Considerable progress in the treatment of renal cell carcinoma over the last years has forced researchers to look for new factors of potential prognostic or predictive value in this tumour type in order to clarify the selection of patients for optimal treatment. The drugs from the group of tyrosine kinase inhibitors have played a decisive role. So far, the Motzer model, grouping the prognostic factors, has been most commonly used in clinical practice. Based on the current research looking for new markers of prognostic or predictive value, these factors can be divided into cellular hypoxia-induced proteins and proteins regulating the cell cycle and the apoptosis process. In the second part of this study, hypoxia-inducible factors will be discussed.